PENGARUH BEBERAPA JENIS PUPUK TERHADAP HASIL TIGA VARIETAS KEDELAI (GLYCINE MAX (L.) MERILL) - Arum Asriyanti Suhastyo; Eko Apriliyanto (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2014)
Fertilization is one way to increase the production of soybeans, with the hope of accelerating the growth and development of plants and to improve the quality and quantity of results. The purpose of the study was to determine the response of soybean plants to variation fertilizer (cow manure, Inorganic fertilizers, MOL and Bio P2000Z ). The research is implemented in the experimental garden plots Polytechnic Banjarnegara use design Divided (Split plot). The treatments tested were 3 varieties of soybean (Menthel, Argomulyo and Burangrang) and 4 types of fertilizers are control/without fertilizer, cow manure 5 tons/ha, NPK fertilizer recommendation (urea 25 kg Ha-1; SP-36 150 kg Ha-1; KCl 100 kg Ha-1), MOL banana weevil (4,8 L Ha-1), P2000Z organic fertilizer (1 L Ha-1). Each treatment was repeated 3 times, so there are 45 experimental units. The results showed local soybean menthel showed the highest results in the total number of pods per plant and dry weight of seeds per plant are consecutive ie 74,92 g pods and 11,12 g. Argomulyo varieties showed the highest yield on a dry weight of 100 seeds in a row is 12,92 g. Cow dung fertilizer, NPK, MO, liquid fertilizer and without fertilizer may not increase plant height, plant dry weight, total number of pods/plant, dry weight of 100 seeds and dry weight of seeds per plant in soybean plants. There is no interaction effect of varieties and fertilizer to all growth parameters and yield of soybean.